Production Performance Analysis to Mature Field Development Plan: Production Performance Analysis to Mature Field Development Plan - Raharjo, Cahyo Tri; Laksmita Sari, Riska (Journal of Sustainable Energy Development, 2024)
The research focuses on evaluating the production performance of three oil wells-Well F55A MB, Well Hovea 13 ST1, and Well Pedirka-1-using Inflow Performance Relationship (IPR) and Vertical Lift Performance (VLP) analysis to determine optimal artificial lift methods for each case. The study explores critical production parameters such as reservoir pressure, temperature, and gas-to-oil ratio (GOR) while employing decision tree methodologies to select suitable artificial lift systems. For Well Hovea 13 ST1 and Well Pedirka-1, gas lift installations significantly enhanced oil recovery rates by optimizing injection pressures and valve placements, achieving production gains of 694 and 300 barrels per day, respectively. In contrast, Well F55A MB, characterized by high water cut and lower reservoir temperatures, was deemed unsuitable for artificial lift based on the decision tree analysis, with a stable production of 2832 stb/d. This work highlights the importance of tailored artificial lift strategies for maximizing oil recovery and improving well performance in diverse reservoir conditions.